The Influence of Work-Life Balance and Self-Regulation on Job Performance of Gen Z in the Creative Industry in Bima City - Mawar Hidayanti; Ovriyadin; Juwani (GoodWill, 2025)
This study aims to analyze the influence of Work-Life Balance and Self-Regulation on the Job Performance of Generation Z employees working in the creative industry in Bima City. Generation Z is known for its unique characteristics, including a strong appreciation for flexible work arrangements, life balance, and the ability to manage oneself independently. This research employs a quantitative approach using the explanatory survey method. Data were collected purposively from respondents aged 18–28 years who had been working for at least six months in the creative industry. The data were gathered through questionnaires and analyzed using multiple linear regression analysis. The results indicate that both Work-Life Balance and Self-Regulation significantly influence Job Performance, both partially and simultaneously. These findings highlight the importance of maintaining a balance between work and personal life, as well as the role of self-regulation in enhancing the job performance of Generation Z. This study is expected to serve as a reference for managers, young employees, and policymakers in developing strategies to improve performance in the creative economy sector.